The Effect of Using The Kinemaster Video Application Among Elementary School Students: Extending The TAM Model - Hanifah May Wisuda Ashari; Zulherman Zulherman (STAI Hubbulwathan Duri, 2022)
The COVID-19 pandemic has changed the arrangement of the learning process, and the animation learning video media has become the alternative solution for the continuity of the learning process. This study aims to develop and test the model empirically to predict the factors influencing students intention behavior on the usage of editing video application (Kinemaster) in the making of learning media animation video. Because Kinemaster application have a complete features in making learning video animation. To explores students intention behavior in accepting and using an editing video application (Kinemaster) based on the user's perspective. By implementing Technology Acceptance Model (TAM), this research studies factors such as trust, motivation, perceived usefulness, perceived ease of use, and interest using the Kinemaster application. The data were obtained through an online survey by spreading the questionnaire to students of grade V in Elementary School and 96 students. Subsequently, the data were analyzed using the partial least square structural modeling (PLS-SEM) approach to test the model and hypothesis. This research result indicates that one hypothesis was rejected (H2), trust - perceived ease of use (P-Value 0.097 0.05), but the other factors imply significant results in accepting and using Kinemaster editing video application to make animation learning videos during the pandemic. The outcome in this study has succeeded in showing the significant influence of Kinemaster application by making learning video animation through TAM model that influences intention behavior on trust and motivation of the elementary students, that proves students creative potential in making video learning animation.